CANCER AND CAM (COMPLEMENTARY AND ALTERNATIVE MEDICINE) PARADOX Ayşe ÖZDEMİR [1] , Yılda Arzu ABA [2] - Ayşe ÖZDEMİR; Yılda Arzu ABA (Rojan GÜMÜŞ, 2016)
Herbal therapy or phyto therapy have been commonly used to treat patients with herbs for thousands of years around the world particularly in such regions as Anatolia and China. Herbal drugs are believed to be useful and harmless among the public. The interaction of herbal products and cancer drugs is a big problem encountered during cancer treatment and its effects are not well-known. Cancer treatment is important and must not be interrupted. In this review, we discussed the paradox of the interaction of herbal products and cancer drugs in the light of experimental and epidemiological evidences as well as the impact of online news regarding the herbal medicines for cancer treatment.